N-Acetyl Cysteine Overdose Inducing Hepatic Steatosis and Systemic Inflammation in Both Propacetamol-Induced Hepatotoxic and Normal Mice - Gunn-Guang Liou; Cheng-Chi Hsieh; Yi-Ju Lee; Pin-Hung Li; Ming-Shiun Tsai; Chi-Ting Li; Sue-Hong Wang (MDPI AG, 2021)
Acetaminophen (APAP) overdose induces acute liver damage and even death. The standard therapeutic dose of N-acetyl cysteine (NAC) cannot be applied to every patient, especially those with high-dose APAP poisoning. There is insufficient evidence to prove that increasing NAC dose can treat patients who failed in standard treatment. This study explores the toxicity of NAC overdose in both APAP poisoning and normal mice. Two inbred mouse strains with different sensitivities to propacetamol-induced hepatotoxicity (PIH) were treated with different NAC doses. NAC therapy decreased PIH by reducing lipid oxidation, protein nitration and inflammation, and increasing glutathione (GSH) levels and antioxidative enzyme activities. However, the therapeutic effects of NAC on PIH were dose-dependent from 125 (N125) to 275 mg/kg (N275). Elevated doses of NAC (400 and 800 mg/kg, N400 and N800) caused additional deaths in both propacetamol-treated and normal mice. N800 treatments significantly decreased hepatic GSH levels and induced inflammatory cytokines and hepatic microvesicular steatosis in both propacetamol-treated and normal mice. Furthermore, both N275 and N400 treatments decreased serum triglyceride (TG) and induced hepatic TG, whereas N800 treatment significantly increased interleukin-6, hepatic TG, and total cholesterol levels. In conclusion, NAC overdose induces hepatic and systemic inflammations and interferes with fatty acid metabolism.